A sustainable modificatory 1, 2- alternate thiacalix[4]arene for detection of silver ion. (February 2023) - Yu, Mei; Liu, Baichen; Guo, Ju; Wu, Fuyong
Abstract: Rational design of 1, 2- alternate thiacalix [4]arene-based fluorophore with efficient detection heavy metal cation (Ag + ) is still challenging. In this paper, a novel thiacalix [4]arene probe (s2 ) connecting a mono- 4-chloro-7-nitrobenzofurazan (NBD-Cl) group substituted with colorimetric and fluorogenic 1, 2- alternate chemosensor which characteristics by UV–vis absorption and fluorescence spectroscopy is synthesized. When s2 reacted with Ag  +  ion, it exhibited highly sensitive ratiometric recognition to Ag  +  ions. Chemosensor s2 has shown a wide dynamic concentration range with a detection limit of 7.6 × 10 −9  M for Ag + in THF/H2 O buffer solution, and the recognition mechanism between s2 and Ag  +  ion has been confirmed by various characterization techniques such as mass spectroscopy and 1 H NMR titrations. Obviously ICT effect took part in banding process from the chemosensor to Ag  +  cation and the formation of 1:1 complex between s2 and Ag + from Job's plot in absorbance and FL spectrum results. Furthermore, the probe s2 also successfully applied to image Ag  +  ion in living PC3 cells. Highlights: A sustainable modificatory 1, 2- alternate thiacalix [4]arene has been designed and synthesized. When the probe reacted with Ag  +  ion, it exhibited highly sensitive ratiometric recognition to Ag + ions. The probe successfully applied to image Ag  +  ion in living PC3 cells.